Replisome Dynamics and Their Functional Relevance upon DNA Damage through the PCNA Interactome - Mrinal Srivastava; Zhen Chen; Huimin Zhang; Mengfan Tang; Chao Wang; Sung Yun Jung; Junjie Chen (Cell Reports, 2018)
Summary: Eukaryotic cells use copious measures to ensure accurate duplication of the genome. Various genotoxic agents pose threats to the ongoing replication fork that, if not efficiently dealt with, can result in replication fork collapse. It is unknown how replication fork is precisely controlled and regulated under different conditions. Here, we examined the complexity of replication fork composition upon DNA damage by using a PCNA-based proteomic screen to uncover known and unexplored players involved in replication and replication stress response. We used camptothecin or UV radiation, which lead to fork-blocking lesions, to establish a comprehensive proteomics map of the replisome under such replication stress conditions. We identified and examined two potential candidate proteins WIZ and SALL1 for their roles in DNA replication and replication stress response. In addition, our unbiased screen uncovered many prospective candidate proteins that help fill the knowledge gap in understanding chromosomal DNA replication and DNA repair. : Srivastava et al. used unbiased PCNA-centered approaches to construct landscapes of replisome complexes with or without replication stress. These findings uncover many known and previously unexplored proteins that are potentially important for the resolution of two different types of replication fork-blocking lesions. Keywords: DNA replication, PCNA, proximity labeling, DNA damage, replication stress